2022
DOI: 10.3899/jrheum.211231
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Disease-Modifying Antirheumatic Drugs for Enthesitis in a Prospective Longitudinal Psoriatic Arthritis Cohort

Abstract: Objective Our objective was to assess the effectiveness of conventional and targeted disease modifying anti-rheumatic drugs (cDMARDs and tDMARDs, respectively) in treating enthesitis in PsA. Methods Patients with active enthesitis, defined as ≥1 tender entheses (of 29 sites included in the spondyloarthritis research consortium of Canada enthesitis index, the Leeds enthesitis index, and the Maastricht ankylosing spondylitis enthesitis score), enrolled in a large PsA cohort were included. Medications at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…The inverse association between remission and baseline activity score was also observed for peripheral arthritis (i.e., DAPSA) [ 30 ]. Data from the University of Toronto PsA clinic reported that the resolution of enthesitis was associated with lower joint activity and male sex [ 31 ]. Similar to our study, they reported that a high CRP level at baseline was associated with a better response to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The inverse association between remission and baseline activity score was also observed for peripheral arthritis (i.e., DAPSA) [ 30 ]. Data from the University of Toronto PsA clinic reported that the resolution of enthesitis was associated with lower joint activity and male sex [ 31 ]. Similar to our study, they reported that a high CRP level at baseline was associated with a better response to therapy.…”
Section: Discussionmentioning
confidence: 99%